Analisis Algoritma J48 Pada Pengambilan Keputusan Pemberian Pinjaman Kepada Calon Nasabah - Silitonga, Agnes Irene; Ginting, Lukas; Sinaga, Enjelina; Zega, Elson; Sembiring, Samuel; Simamora, Yoakim (Universitas Methodist Indonesia, 2024)
This research aims to analyze the stages of decision making for granting loans to prospective customers using the J48 Algorithm. Using the